2016
DOI: 10.1016/j.jnucmat.2015.10.049
|View full text |Cite
|
Sign up to set email alerts
|

In situ synchrotron tensile investigations on 14YWT, MA957, and 9-Cr ODS alloys

Abstract: Advanced ODS alloys provide exceptional radiation tolerance and high-temperature mechanical properties when compared to traditional ferritic and ferritic/martensitic (F/M) steels. Their remarkable properties result from ultrahigh density and ultrafine size of Y-Ti-O nanoclusters within the ferritic matrix. In this work, we applied a high-energy synchrotron radiation X-ray to study the deformation process of three advanced ODS materials including 14YWT, MA957, and 9-Cr ODS steel. Only the relatively large nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 68 publications
1
8
1
Order By: Relevance
“…4(c1)). Similar behavior of internal stress development has been observed in many of the materials with multiple phases: the lattice strain of the metallic matrix slightly decreases during early yielding, but increases afterwards until necking [30]…”
Section: Macro-scale Tensile Deformationsupporting
confidence: 72%
See 1 more Smart Citation
“…4(c1)). Similar behavior of internal stress development has been observed in many of the materials with multiple phases: the lattice strain of the metallic matrix slightly decreases during early yielding, but increases afterwards until necking [30]…”
Section: Macro-scale Tensile Deformationsupporting
confidence: 72%
“…Previous studies have shown that the nanoclusters in both 14YWT and MA957 were invisible in the XRD diffraction measurement due to their non-stoichiometric nature. As the direct lattice strain measurements of nanoclusters are not applicable [30] the mean internal stresses of the ferritic matrix and strengthening factors (SFs) [31] were calculated to represent the strengthening effect of the nanoclusters during plastic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Research works are still very active and versatile in the experimental mechanics field. Deformation and fracture are still common interest for metals and alloys [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], foams and porous materials [ 11 , 14 , 43 , 44 , 45 , 46 ], and composites [ 13 , 47 , 48 , 49 ]. XRT has also been considerably extended with other in situ measurements including materials processing [ 50 , 51 , 52 , 53 , 54 , 55 ], materials interaction with specified conditions involving extreme temperature [ 56 , 57 ], corrosion [ 58 , 59 , 60 ], electrochemical environments, as in batteries [ 61 , 62 , 63 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of this difference in nanoparticle morphology between austenitic and F/M ODS steels can be determined using the APT results. [14,20]. In addition, due to the scattered Y/Ti ratios for the nanoparticles with a radii smaller than 4 nm, pyrochlore and orthorhombic structures can also be occasionally observed, as reported by Chen et al [30] and Cunningham [31].…”
Section: Discussionmentioning
confidence: 57%
“…Although pyrochlore structured nanoparticles were occasionally observed within this size range [30], this was only for a small fraction of the nanoparticles, whereas the majority fail to exhibit a well-defined crystal structure [31]. Recent synchrotron X-ray scattering results [20] show that Y-Ti-O enriched nanoparticles smaller than approximately 4 nm in radius do not contribute to the formation of diffraction peaks corresponding to either Y 2 Ti 2 O 7 or Y 2 TiO 5 , further supporting the current observation that nanoparticles smaller than 4 nm rarely have a well-defined crystalline structure. On the contrary, the majority of the nanoparticles (around 100 observed in HRTEM experiments) in an ODS 316 steel that have radii ranging from 2 nm to 4 nm were indexed consistent with a pyrochlore structure, as reported by…”
Section: Resultsmentioning
confidence: 99%